MicroRNAs in breast cancer: oncogene and tumor suppressors with clinical potential - Wang, Wei (Zhejiang University Press, 2015)

(untitled) (J Zhejiang Univ Sci B)
MicroRNAs (miRs) are small single-stranded RNA molecules, which function as key negative regulators of post-transcriptional modulation in almost all biological processes. Abnormal expression of microRNAs has been observed in various types of cancer including breast cancer. Great efforts have been made to identify an association between microRNA expression profiles and breast cancer, and to understand the functional role and molecular mechanism of aberrant-expressed microRNAs. As research progressed, ‘oncogenic microRNAs’ and ‘tumor suppressive microRNAs’ became a focus of interest. The potential of candidate microRNAs from both intercellular (tissue) and extracellular (serum) sources for clinical diagnosis and prognosis was revealed, and treatments involving microRNA achieved some amazing curative effects in cancer disease models. In this review, advances from the most recent studies of microRNAs in one of the most common cancers, breast cancer, are highlighted, especially the functions of specifically selected microRNAs. We also assess the potential value of these microRNAs as diagnostic and prognostic markers, and discuss the possible development of microRNA-based therapies.